MOTIVASI PETANI DALAM PENANAMAN PADI PANDANWANGI (Suatu Kasus Petani Kecamatan Warungkondang Kabupaten Cianjur, Jawa Barat) - Cut Shabilla Irvany; Yayat Sukayat (Universitas Galuh, 2022)
In macro terms, the increase in population will be directly proportional to the need for food. Even if traced on a micro basis, there has been a decline in the level of rice consumption per capita. In 2016 rice consumption was 124.89 kg per capita per year, while in 2017 it was 114.6 kg per year (Ministry of Agriculture, 2017). The rice varieties cultivated by farmers consist of varieties that produce medium, premium and special rice. Rice varieties that are included in a special category with limited interest are pandanwangi rice/rice. The question is what is the motivation of farmers to cultivate Pandanwangi Rice. The purpose of this study was to determine the motivation of farmers to plant pandanwangi rice. This study uses a quantitative research design with survey techniques on 88 sample farmers, cases in the famous warung subdistrict, Cianjur Regency. From the research results, the motivation of farmers to plant pandanwangi rice is because they want to maintain Cianjur as a pandanwangi rice producing area. Farmers feel proud of pandanwangi rice which can only be grown in Cianjur and is a characteristic of Cianjur district.